Keep moving : and other tips and truths about aging - Van Dyke, Dick; Gold, Todd (Weinstein Books, 2015)
"In a fun and folksy way of addressing readers, Keep Moving will serve as an instruction book on how to embrace old age with a positive attitude. The chapters are filled with exclusive personal anecdotes that explore various themes on aging: how to adapt to the physical and social changes, deal with loss of friends and loved ones, stay current, fall in love again, and "keep moving" every day like there's no tomorrow,"--Amazon.com.